2006
DOI: 10.1074/jbc.m602374200
|View full text |Cite
|
Sign up to set email alerts
|

Auto-activation of the Apoptosis Protein Bax Increases Mitochondrial Membrane Permeability and Is Inhibited by Bcl-2

Abstract: Interactions among Bcl-2 family proteins mediated by Bcl-2 homology (BH) regions transform apoptosis signals into actions.The interactions between BH3 region-only proteins and multi-BH region proteins such as Bax and Bcl-2 have been proposed to be the dominant interactions required for initiating apoptosis. Experimental evidence also suggests that both homo-and hetero-interactions are mediated primarily by the BH3 regions in all Bcl-2 family proteins and contribute to commitment to or inhibition of apoptosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
148
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 64 publications
(102 reference statements)
6
148
2
1
Order By: Relevance
“…In that case, the exposed Bax BH3 domain would act just like the BH3 domain of a direct activator BH3-only protein. This would be consistent with the observation that a small number of BH3-only proteins can recruit a molar excess of Bax to the membrane through a Bax-autoactivating mechanism (Tan et al 2006). Indeed, experimental evidence obtained with a stapled Bax BH3 peptide similar to the Bim peptide described above suggests self-propagating autoactivation of Bax (Gavathiotis et al 2010).…”
Section: Structural Reorganization Of Bax/bak During Activationsupporting
confidence: 73%
See 1 more Smart Citation
“…In that case, the exposed Bax BH3 domain would act just like the BH3 domain of a direct activator BH3-only protein. This would be consistent with the observation that a small number of BH3-only proteins can recruit a molar excess of Bax to the membrane through a Bax-autoactivating mechanism (Tan et al 2006). Indeed, experimental evidence obtained with a stapled Bax BH3 peptide similar to the Bim peptide described above suggests self-propagating autoactivation of Bax (Gavathiotis et al 2010).…”
Section: Structural Reorganization Of Bax/bak During Activationsupporting
confidence: 73%
“…Bax is subsequently recruited by tBid and integrates into the membrane, which can be inhibited by the addition of Bcl-XL. When Bax becomes activated at the membrane, the rate-limiting step is its oligomerization, which involves the recruitment and activation of more Bax molecules (Tan et al 2006;Lovell et al 2008). While Bax oligomerizes, liposome contents are released because of membrane permeabilization at the same time.…”
Section: Models For Interaction Between Bcl-2 Proteinsmentioning
confidence: 99%
“…S7D). Finally, to explore whether the distinct trigger sites for initiating direct activation of BAK/BAX by BID/BIM BH3 helices are invoked during the self-propagation and/or oligomeric self-association steps of BAK/BAX activation (28,40,41), we generated BAK and BAX pSAHBs corresponding to the BAK and BAX BH3 helices for crosslinking analyses. Consistent with the results observed for BID and BIM pSAHBs, BAK and BAX pSAHBs crosslinked exclusively to residues of the canonical BH3-binding pocket of FL-BAK (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 However, some recent reports have indicated that p53 can mediate apoptosis when engaged directly from the cytoplasm. [12][13][14] Therefore, changes in the subcellular distribution of p53 partly contribute to its function. 15,16 Little is known about whether the overexpression of low risk E6 protein alters the distribution of p53 protein, and what happens next.…”
Section: Introductionmentioning
confidence: 99%